La estimulación temprana y su influencia en el desarrollo de la psicomotricidad en los niños y niñas con retraso motor de 0 a 3 años de edad, que acuden al centro de rehabilitación médica n°1 del ministerio de salud pública, del distrito metropolitano de Quito periodo 2013 - Mendoza Reinoso, Olga Janneth (2014)
his research work is called " EARLY STIMULATION AND ITS INFLUENCE ON THE DEVELOPMENT OF PSYCHOMOTRICITY IN CHILDREN WITH MOTOR DELAY OF 0 TO 3 YEARS OF AGE WHO GO TO MEDICAL REHABILITATION CENTER no.1 MINISTRY OF HEALTH PUBLIC , METROPOLITAN DISTRICT OF QUITO PERIOD 2013 " . This research has a general objective : Achieve the normal child growth engine development through early stimulation and their influence on psychomotor development in children with motor delay 0-3 years old, attending the Medical Rehabilitation center no.1 Ministry of Public Health, the Metropolitan District of Quito period 2013. The methods and techniques used for this research work were: the Scientific Method , Inductive- Deductive and Statistical Model , techniques and tools used in the investigation were : The Interview physiotherapist applied to the Medical Rehabilitation Centre N. - 1 of the Ministry Public Health , in order to know the techniques used in the early stimulation applied to survey parents to establish community needs to create new centers of stimulation and guidance of Portage, to diagnose the development engine and determine the progress of the children after receiving therapy. With guidance from portage was found, the progress that has managed to achieve with the children after performing therapies, it can be said that in 2 of the children investigated by 100 % significant progress was achieved and 85% corresponding to 1 girl investigated no progress was achieved in full. With the application of the interview it was learned that the most commonly used with children with motor delay problem by therapists in the rehabilitation center techniques are: Bobath therapy, music therapy and occupational therapy . With the survey of parents 100 % consider the need for the creation of new centers of early stimulation in the sector for the prevention and treatment of motor problems.